Three-dimensional full loop modeling and optimization of an in situ gasification chemical looping combustion system - Shao, Yali; Zhang, Yong; Wang, Xiaojia; Wang, Xudong; Jin, Baosheng; Liu, Hao (American Chemical Society, 2017)
This study presents a comprehensive three-dimensional full loop simulation on a novel in situ gasification chemical looping combustion (iG-CLC) system. This iG-CLC model mainly consists of a high-flux circulating fluidized bed fuel reactor, a counter-flow moving bed air reactor, an inertial separator, a J-valve, and a downcomer. The Eulerian–Eulerian two-fluid model incorporated with the standard k–ε turbulence model for the gas phase and the kinetic theory of granular flow for the solid phase was applied to model the gas–solid flow dynamics characteristics in the whole system. The quasi-stable solid circulation in the whole system could be realized after about 20 s of the computational time with the Gidaspow drag model and the specularity coefficient of 0.5, in which the fuel reactor and air reactor achieved intense turbulence flow and steady near plug flow, respectively. However, when the AR inlet gas flow exceeded a critical value, the stable flow state in the AR would be destroyed due to the appearance of bubbles. Further, a two-stage AR was proposed and coupled into the original system, which successfully improved the AR carrying capacity of gas flow.